Study of follistatin and sex hormones level in women with polycystic ovarian sayndrome in Baghdad - Ikhlass Abdul wahab Maarouf; Zaid Mohamad Mubarak (Tikrit Journal of Pure Science)
The aim of this search was to study the levels of follistatin and a number of sex hormones of polycystic ovary syndrome patients (PCOS).The study included 70 blood samples of women infected with PCOS and 20 samples from healthy women as control. The study had been perfigureed in Baghdad / Kamal al-Samarrai Hospital. The patient had been diagnosed with ultrasound waves (sonar device) by specialized physicians in the hospital. The research requirements for the period from September 2016 to March 2017. The results showed high significant difference (p <0.01) in the concentration of follistatin in women with PCOS compared with healthy women. On the other hand, there was a significant decrease (p <0.01) in the concentration of follicle stimulating hormone (FSH) in women with PCOS compared to control. The results showed high significant increase (P<0.01) in the concentrations of prolactin hormone and testosterone hormone  in patients with PCOS compared to control.